Prevalência de asma e fatores de risco em escolares da cidade de São Paulo Asthma prevalence and risk factors in schoolchildren of the city of São Paulo, Brazil - Rejane R D Casagrande; Antonio C Pastorino; Renata G L Souza; Cláudio Leone; Dirceu Solé; Cristina M A Jacob (Universidade de São Paulo, 2008)
OBJETIVO: Analisar a prevalência de asma e possíveis fatores de risco associados. MÉTODOS: Estudo transversal, integrante do International Study of Asthma and Allergies in Childhood. Participaram 561 escolares de seis a sete anos de idade, provenientes de 35 escolas públicas da cidade de São Paulo, escolhidas por sorteio, em 2002. A amostra incluiu 168 asmáticos e 393 não asmáticos, que responderam questionário constituído por 33 questões referentes a dados pessoais, familiares e ambientais. A associação entre asma e fatores de risco foi avaliada pela análise de regressão logística, considerando-se nível de significância estatística de 5%. RESULTADOS: Entre os escolares, 31,2% referiam sibilos nos 12 meses anteriores à entrevista. Os fatores de risco significativamente associados à asma foram: sexo masculino (OR=2,4;IC 95%: 1,4;4,2), mãe fumante no primeiro ano de vida (OR=2,0; IC 95%: 1,1;3,8), presença de eczema em locais característicos (OR=3,0; IC 95%:1,2; 7,6) e rinoconjuntivite (OR=2,4;IC 95%: 1,2; 4,8). CONCLUSÕES: A prevalência de asma na região estudada foi elevada e os fatores de risco relacionados foram: sexo masculino, sintomas de rinoconjuntivite no último ano, mãe fumante no primeiro ano de vida e presença de eczema em locais característicos. OBJECTIVE: To assess asthma prevalence and potential risk factors associated. METHODS: Cross-sectional study part of the International Study of Asthma and Allergies in Childhood. A total of 561 schoolchildren aged 6-7 years from 35 public schools in the city of São Paulo (Southeastern Brazil) were drawn to participate in the study, in 2002. The sample consisted of 168 asthmatic and 393 non-asthmatic children who answered a questionnaire comprising 33 questions on personal, family and environmental information. The association between asthma and the risk factors studied was assessed by logistic regression analysis at a 5% statistical significance. RESULTS: Among the schoolchildren studied, 31.2% reported wheezing in the 12 months preceding the interview. The following risk factors were significantly associated with asthma: male gender (OR=2.4; 95% CI: 1.4;4.2), maternal smoking in the child's first year of life (OR=2.0; 95% CI: 1.1;3.8), eczema on characteristic body areas (OR=3.0; 95% CI: 1.2;7.6) and rhinoconjunctivitis (OR=2.4; 95% CI: 1.2;4.8). CONCLUSIONS: Asthma prevalence in the study area was high and the risk factors identified were male gender, rhinoconjunctivitis in last year, maternal smoking in the child's first year of life and eczema on characteristic body areas.